Ethylene from sugar-cane alcohol - Floro, Manuel R. (College of Engineering, 1969)
It is the aim of this project study to investigate the possibility of establishing an ethylene plant after a poly-ethylene plant has been established, considering that this would be the first in the Philippines. Local production of this important petrochemical would not only eliminate increasing importation of ethylene but also initiate development of the polyethylene plastic industry in the country.